Research of the interaction of public-private partnership as a tool of development of alternative energy - Riazanova, Nataliia (Technology audit and production reserves, 2018)
The object of research is a public-private partnership (PPP) as a tool for strategic management of alternative energy development. One of the most problematic places is the identification of functions, areas and ways of PPP interaction. The program-targeted research method, along with other used methods, allows determining priority directions for the effectiveness of PPP interaction as a tool for strategic management of alternative energy development. And also to make a choice of organizational ways of PPP development and to formulate the PPP concept. The study used the methods of system-structural, spatial analysis, logical generalization, synthesis, comparison, induction and deduction are used for preliminary analysis of the problem statement formation and the definition of goals. The essence of the “public-private partnership”, “partnership” concepts is defined, autonomous state functions are investigated. Characteristics are defined regarding the advantages of partners from participating in joint projects using the method of analogies and comparative comparison. The definition of directions of regulation of partnerships from the public sector is obtained. This is due to the fact that the proposed method has a number of features that emerge in developing a strategy and principles for building interaction relations, facilitating the formation of an effective institutional environment and the development by the state of forms, methods and specific mechanisms for PPP interaction. The organizational paths for the PPP development as a tool for the strategic management of alternative energy development are determined, which note that public sector participation extends to the level of obtaining a blocking minority. Thus, the state has a sufficient degree of influence. This ensures the possibility of timely, proper and skillful use of certain functions, areas and ways of PPP interaction as a tool for the strategic management of the development of alternative energy. This ensures the activation of innovation and investment activities and in the shortest possible time to achieve favorable economic indicators in the energy sector, both at the level of individual regions and the state as a whole, which contributes to the sustainable development of the country’s economy.